2021
DOI: 10.1021/acscatal.1c03691
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450-Catalyzed Biosynthesis of a Dihydrofuran Neoclerodane in Magic Mint (Salvia divinorum)

Abstract: The hallucinogenic plant, Salvia divinorum, synthesizes neoclerodane diterpenes, such as salvinorins, salvidivins, and salvinicins, which are agonistic or antagonistic to μor κ-opioid receptors. From S. divinorum trichomes, crotonolide G synthase (SdCS; CYP76AH39) was identified. It catalyzes the conversion of kolavenol to a dihydrofuran neoclerodane, crotonolide G. 18 O 2feeding studies confirmed that SdCS incorporates an aerobic oxygen into crotonolide G, rather than forming a cation at C16 that is trapped b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Although in S. splendens the dedicated KLS SspdiTPS1.5 is placed in the clade with other class I diTPS that act on CPP, it is phylogenetically distant (Figure 5A) from the promiscuous miltiradiene synthase SspdiTPS1.3 which also shows KLS enzymatic activity, and from the KLS/IKLS enzymes from Scutellaria species. The paired activity of class II and class I diTPS in plastids, is essential for the generation of kolavenol and later utilization by downstream enzymes (De La Peña and Sattely, 2021; Kwon et al ., 2022). The phylogeny of class I clerodane synthases supports the polyphyletic origin of clerodane biosynthetic pathway in the family Lamiaceae.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although in S. splendens the dedicated KLS SspdiTPS1.5 is placed in the clade with other class I diTPS that act on CPP, it is phylogenetically distant (Figure 5A) from the promiscuous miltiradiene synthase SspdiTPS1.3 which also shows KLS enzymatic activity, and from the KLS/IKLS enzymes from Scutellaria species. The paired activity of class II and class I diTPS in plastids, is essential for the generation of kolavenol and later utilization by downstream enzymes (De La Peña and Sattely, 2021; Kwon et al ., 2022). The phylogeny of class I clerodane synthases supports the polyphyletic origin of clerodane biosynthetic pathway in the family Lamiaceae.…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 26, 2022. ; https://doi.org/10.1101/2022.09.25.509435 doi: bioRxiv preprint Scutellaria species. The paired activity of class II and class I diTPS in plastids, is essential for the generation of kolavenol and later utilization by downstream enzymes (De La Peña and Sattely, 2021; Kwon et al, 2022). The phylogeny of class I clerodane synthases supports the polyphyletic origin of clerodane biosynthetic pathway in the family Lamiaceae.…”
Section: Mussini)mentioning
confidence: 99%
See 2 more Smart Citations
“…Crotonolide G synthase (SdCS), a cytochrome P450 enzyme from Salvia divinorum , has been shown to catalyse the formation of the dihydrofuran of crotonolide G 29 from kolavenol 28 (Scheme 1) during the biosynthesis of diterpenes such as salvinorins, salvidivins and slavinicins. 21 Feeding studies using 18 O 2 , revealed that SdCS facilitates incorporation of an aerobic oxygen atom at C-16 of 28 , with dihydrofuran formation then achieved by nucleophilic attack of the resulting alcohol on the activated C-15 hydroxyl group. Genome mining and activation of a cryptic polyketide synthase gene from Aspergillus hancockii has allowed the discovery of hancockinone A 30 , a prenylated polycyclic aromatic polyketide with a 6/6/6/5 skeleton.…”
mentioning
confidence: 99%